Molecular remission is an independent predictor of clinical outcome in patients with mantle cell lymphoma after combined immunochemotherapy: a European MCL intergroup study - Pott, Christiane; Hoster, Eva; Delfau-Larue, Marie-Helene; Beldjord, Kheira; Böttcher, Sebastian; Asnafi, Vahid; Plonquet, Anne; Siebert, Reiner; Callet-Bauchu, Evelyne; Andersen, Niels; van Dongen, Jacques J. M.; Klapper, Wolfram; et al. (Blood, 2010)
The prognostic impact of minimal residual disease (MRD) was analyzed in 259 patients with mantle cell lymphoma (MCL) treated within 2 randomized trials of the European MCL Network (MCL Younger and MCL Elderly trial). After rituximab-based induction treatment, 106 of 190 evaluable patients (56%) achieved a molecular remission (MR) based on blood and/or bone marrow (BM) analysis. MR resulted in a significantly improved response duration (RD; 87% vs 61% patients in remission at 2 years, P = .004) and emerged to be an independent prognostic factor for RD (hazard ratio = 0.4, 95% confidence interval, 0.1-0.9, P = .028). MR was highly predictive for prolonged RD independent of clinical response (complete response [CR], complete response unconfirmed [CRu], partial response [PR]; RD at 2 years: 94% in BM MRD-negative CR/CRu and 100% in BM MRD-negative PR, compared with 71% in BM MRD-positive CR/CRu and 51% in BM MRD-positive PR, P = .002). Sustained MR during the postinduction period was predictive for outcome in MCL Younger after autologous stem cell transplantation (ASCT; RD at 2 years 100% vs 65%, P = .001) and during maintenance in MCL Elderly (RD at 2 years: 76% vs 36%, P = .015). ASCT increased the proportion of patients in MR from 55% before high-dose therapy to 72% thereafter. Sequential MRD monitoring is a powerful predictor for treatment outcome in MCL. These trials are registered at www.clinicaltrials.gov as #NCT00209222 and #NCT00209209.
Vorveröffentlicht als "Blood First Edition paper": 23. Dezember 2009
Gesehen am 05.05.2023